Osteoblastic STAT3 Is Crucial for Orthodontic Force Driving Alveolar Bone Remodeling and Tooth Movement. (13th December 2022) - Gong, Xinyi; Sun, Siyuan; Yang, Yiling; Huang, Xiangru; Gao, Xin; Jin, Anting; Xu, Hongyuan; Wang, Xijun; Liu, Yuanqi; Liu, Jingyi; Dai, Qinggang; Jiang, Lingyong
ABSTRACT: Mechanical force is essential to shape the internal architecture and external form of the skeleton by regulating the bone remodeling process. However, the underlying mechanism of how the bone responds to mechanical force remains elusive. Here, we generated both orthodontic tooth movement (OTM) model in vivo and a cyclic stretch‐loading model in vitro to investigate biomechanical regulation of the alveolar bone. In this study, signal transducer and activator of transcription 3 (STAT3) was screened as one of the mechanosensitive proteins by protein array analysis of cyclic stretch‐loaded bone mesenchymal stem cells (BMSCs) and was also proven to be activated in osteoblasts in response to the mechanical force during OTM. With an inducible osteoblast linage‐specific Stat3 knockout model, we found that Stat3 deletion decelerated the OTM rate and reduced orthodontic force‐induced bone remodeling, as indicated by both decreased bone resorption and formation. Both genetic deletion and pharmacological inhibition of STAT3 in BMSCs directly inhibited mechanical force‐induced osteoblast differentiation and impaired osteoclast formation via osteoblast–osteoclast cross‐talk under mechanical force loading. According to RNA‐seq analysis of Stat3 ‐deleted BMSCs under mechanical force, matrix metalloproteinase 3 ( Mmp3) was screened and predicted to be a downstream target of STAT3 . The luciferase and ChIP assays identified that Stat3 could bind to the Mmp3 promotor and upregulate its transcription activity. Furthermore, STAT3‐inhibitor decelerated tooth movement through inhibition of the bone resorption activity, as well as MMP3 expression. In summary, our study identified the mechanosensitive characteristics of STAT3 in osteoblasts and highlighted its critical role in force‐induced bone remodeling during orthodontic tooth movement via osteoblast–osteoclast cross‐talk. © 2022 American Society for Bone and Mineral Research (ASBMR).